2002
DOI: 10.1135/cccc20021061
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Electronic Interactions Between closo-Boranes and Triple-Bonded Substituents

Abstract: Intramolecular electronic interactions were investigated in five series of 12-, 10-, and 6-vertex closo-boranes and hydrocarbons (benzene, acetylene, bicyclo[2.2.2]octane, and cubane) substituted with triple-bonded groups Y≡Z (C≡CR, C≡N, C≡O, and N≡N). Structural data (single crystal X-ray crystallography), spectroscopic properties (UV, IR, and NMR), chemical behavior (dediazoniation reactions), and electronic structure calculations (hybridization and π bond order) are all in agreement that the degree of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 61 publications
8
71
0
Order By: Relevance
“…The protected acetylenes 2 and 6 were likewise obtained from sequential reaction of 8 and 10 with methyllithium and chlorotrimethylsilane. The overall yields of 1, 2, 6 and 7 from para-carboranes 3 and 5 are 69%, 67%, 63% and 48%, respectively, which are superior to reported yields of up to 26% from previous single/two-step syntheses [6][7][8]10]. The convenience of a two-step route is also an obvious advantage in effort and cost over the more elaborate multi-step syntheses, which afford the ethynyl carboranes in comparable yield to those described here [9].…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…The protected acetylenes 2 and 6 were likewise obtained from sequential reaction of 8 and 10 with methyllithium and chlorotrimethylsilane. The overall yields of 1, 2, 6 and 7 from para-carboranes 3 and 5 are 69%, 67%, 63% and 48%, respectively, which are superior to reported yields of up to 26% from previous single/two-step syntheses [6][7][8]10]. The convenience of a two-step route is also an obvious advantage in effort and cost over the more elaborate multi-step syntheses, which afford the ethynyl carboranes in comparable yield to those described here [9].…”
Section: Resultssupporting
confidence: 51%
“…As previously noted for other pairs of 10-and 12-vertex cage derivatives [8][9][10]12], the single bond C1-C2 between the ethene and cage is longer in the 12-vertex 8 than in the 10-vertex 10 with values of 1.495(2) and 1.479(3) Å for 8 and 10, respectively. The influence of the substituents on the cage geometry of 1,12-disubstituted-para-carboranes has been discussed in detail elsewhere [7].…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Kaszynski and coworkers investigated the electronic interactions between closo-boron clusters of 6, 10, and 12 vertices (see Figure 2) linked by alkynyl and other triple-bonded groups, using UV, IR, and NMR spectroscopic data and theoretical calculations, and concluded that the electronic conjugation between the clusters and the linkers is greatest for the 6-vertex cages (92). Similar studies demonstrated that the 1,12-C 2 B 10 H 12 ( pcarborane) polyhedron transmits electronic effects, although the mechanism was not established (93).…”
Section: Chains Rings Rods and Boxes: Boron Clusters As Building Bmentioning
confidence: 99%